PENYULUHAN STRATEGI PENJUALAN PRODUK LOKAL UMKM BALAIDESA TLASIH TULANGAN SIDOARJO JAWA TIMUR DALAM MENINGKATKAN PENGHASILAN - Qibliyah, Mariyatul; Izzazi, Zsa Zsa (PUTRA JAWA PUBLISHER, 2024)
In this part, the MSMEs in Tlasih Tulangan village work as entrepreneurs who take advantage of opportunities and use raw materials from nature. Most of the production and various products sold by MSMEs are still produced manually and there are not many of them, so the sales capacity still uses manual or human labor to make the products.Qualitative descriptive research is a research approach that aims to describe and understand a phenomenon or event in depth. This approach focuses more on explaining and understanding how a phenomenon occurs, how people experience it, and how meaning is formed from the participant's perspective. Qualitative descriptive research usually involves collecting data in the form of words, images, or actions from participants, and data analysis is carried out subjectively, primarily through techniques such as in-depth interviews, participant observation, and content analysis. The counseling given to Tlangsih Bone MSMEs aims to ensure that in the long term they will be able to know carefully and accurately how their sales results will increase by 50% from normal income before the advent of e-commerce. The impact of the increase in MSMEs themselves will feel prosperity from a social and economic perspective to meet business needs and be able to expand employment opportunities. Sales Development Strategy The use of sales development strategies that will be provided in this method is product, place, price, promotion, each of which must be able to obtain well implemented as one type of stage, the core priority of product sales can increase drastically